2012
DOI: 10.1159/000343034
|View full text |Cite
|
Sign up to set email alerts
|

Can Early B-Type Natriuretic Peptide Assays Predict Symptomatic Patent Ductus Arteriosus in Extremely Low Birth Weight Infants?

Abstract: Background: Earlier and more accurate identification of a high-risk group of preterm infants that are likely to develop a hemodynamically significant patent ductus arteriosus (hsPDA) would allow specific targeting of early treatment and thus possibly minimize the morbidity and mortality associated with a PDA in extremely low birth weight (ELBW) infants. Objective: To investigate the predictability of B-type natriuretic peptide (BNP) for early targeted treatment of hsPDA in ELBW infants. Methods: 73 ELBW infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
3
19
1
1
Order By: Relevance
“…In this study no difference in PDA occurrence was found. We did find, as did a study by Lee et al [25], early BNP elevation to be related to hsPDA in the AGA group. Although this is an interesting find, it is beyond the scope of this paper.…”
Section: Discussionsupporting
confidence: 86%
“…In this study no difference in PDA occurrence was found. We did find, as did a study by Lee et al [25], early BNP elevation to be related to hsPDA in the AGA group. Although this is an interesting find, it is beyond the scope of this paper.…”
Section: Discussionsupporting
confidence: 86%
“…Serum BNP levels are significantly increased in patients with hemodynamically symptomatic PDA requiring indomethacin administration and/or surgical ligation compared to those with asymptomatic PDA [12]. In this setting, BNP levels may have predictive value in determining those infants likely to develop hemodynamic changes necessitating treatment [13]. BNP levels are also elevated in PPHN [4], with levels correlating with clinical rebound as well as normalization of pulmonary pressures following therapeutic intervention [14].…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (24) suggested that the BNP levels correlated well with the magnitude of the ductal shunt, and the BNP levels were higher in the symptomatic PDA group when compared with the asymptomatic PDA group. Other researchers suggested that the early BNP level was significantly correlated with the magnitude of the ductal shunt and can help to predict hsPDA (2526). Because we could get the BNP level in only 14 infants among the study population (data are not shown), we could not examine such a correlation between the BNP level and other echocardiographic or radiographic parameters or the association between the severity of the clinical symptoms and the BNP level.…”
Section: Discussionmentioning
confidence: 99%